Examining the impact of physical function performance in predicting patient outcomes after lung-sparing surgery for malignant pleural mesothelioma. Issue 22 (23rd October 2022) - Ho, Simon; Culligan, Melissa; Friedberg, Joseph; Goloubeva, Olga; Marchese, Victoria
ABSRACT: Purpose: The purpose of this study was to examine the impact of physical function performance and pulmonary function on patient outcomes after lung-sparing surgery for malignant pleural mesothelioma (MPM). Materials and methods: A retrospective review of 54 patients with MPM from 2015 to 2020 was performed. The primary objective was to assess whether physical function, as measured by the Eastern Cooperative Oncology Group Performance Status (ECOG), and pulmonary function tests were predictive of postoperative patient outcomes (ventilator days, chest tube days, hospital length of stay). A secondary objective was to explore demographic and preoperative variables that best predict postoperative physical function and patient outcomes. Results: Data include 54 patients who underwent extended pleurectomy-decortication. Preoperative ECOG was a significant predictor of postoperative patient outcomes while preoperative lung function lacked predictive ability. Preoperative ECOG was also predictive of preoperative lung function. Age on the day of surgery was the best predictor of postoperative physical function, which was significantly reduced postoperatively. Conclusions: Preoperative physical function performance was a significant predictor of postoperative outcomes. The results of our study highlight the importance of physical function in patients with MPM and support the need for early rehabilitation and further research to determine optimal rehabilitation interventions. IMPLICATIONS FOR REHABILITATION: Preoperative physical function can predict outcomes after lung-sparing surgery for malignant pleural mesothelioma (MPM). Physical function in patients with MPM should be carefully examined. To accurately reflect patients' abilities, patient assessment should include both patient-reported outcomes and performance-based measures. Patients with MPM should receive rehabilitation early after diagnosis and throughout the continuum of care.